2014
DOI: 10.1021/jp502375r
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Property Investigations of TDO in Aqueous Phase by Density Functional Theory, UV Absorption, and Raman Spectroscopy

Abstract: Density functional theory, UV absorption, and Raman spectroscopy are used to investigate the structure and properties of TDO in aqueous solution. The equilibrium structures, UV absorption spectra, interaction energies, and Raman spectroscopy data of TDO, AIMSA, and 12 TDO or AIMSA clusters are calculated. Raman spectroscopy experiments are carried out by 488 and 208 nm laser excitation. The Raman spectra of TDO in solid and aqueous phases have been compared, and the most possible structure for TDO in aqueous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…One reasonable possibility is that TDO changes from a less reactive form (oligomeric) to a more reactive form upon dissolution of the solid in aqueous solution. [38] Unfortunately, there is no way to distinguish between these possibilities in our kinetic measurements; consequently, TDO and AIMSA in the kinetic model may also mean two different forms of thiourea dioxide, not specifically the dioxide and the aminoimino form. Our calculations also indicated that the transformation of two different forms of TDO is accelerated by an increase of pH, which is reflected by the k 1 Ј value indicated in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…One reasonable possibility is that TDO changes from a less reactive form (oligomeric) to a more reactive form upon dissolution of the solid in aqueous solution. [38] Unfortunately, there is no way to distinguish between these possibilities in our kinetic measurements; consequently, TDO and AIMSA in the kinetic model may also mean two different forms of thiourea dioxide, not specifically the dioxide and the aminoimino form. Our calculations also indicated that the transformation of two different forms of TDO is accelerated by an increase of pH, which is reflected by the k 1 Ј value indicated in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that aging effect can be explained not only by formation of AIMSA, but also an initial formation of TDO oligomers in aqueous solution to be different from that of found in solid state. Indeed, recent investigations of TDO in aqueous solutions by DFT, UV, and Raman spectroscopy showed that when TDO is dissolved in water its molecular structure changes significantly 31b…”
Section: Stability and Reactivitymentioning
confidence: 99%
“…The first important fact that one should take care of is that TDOeven acidic conditionsrelatively slowly but steadily rearranges into a more reactive form, whose reactions are reported to be much faster with the corresponding oxidants than the original form of TDO. It is still unresolved whether this rearrangement is the consequence of a tautomerism , or of an oligomer–monomer degradation or even of an aminoimino–carbenoid transformation; it is indisputably clear that this characteristic must be taken into consideration when the kinetics of the redox transformation of TDO is designed to be investigated. Overlooking the possible kinetic effect of aging is not the only inconsistency that may be found.…”
Section: Introductionmentioning
confidence: 99%